Pelestarian Pengetahuan Asli Pande Besi sebagai Sumber Belajar Kimia Unsur Periode IV - Ismawati, Riva; Rahayu, Rina; Muna, Lutfi Kaedzorotul (Chemistry Education Department of Education and Teaching Faculty, 2023)
Ethnoscience is a study that includes original knowledge of the community which can be verified through scientific methods. This original knowledge can be used as a learning resource to provide in-depth experiences, broaden knowledge, and increase students' interest in studying science. The purpose of this research is to reconstruct the original blacksmith's knowledge into scientific knowledge. This study used a qualitative approach with interview and observation methods. The population used in this research is the people of Rejosari Village, Pakis District, Magelang Regency who work as blacksmiths. The focus of research is on the tools and materials used by blacksmiths during the production process. Data analysis uses the Miles-Huberman model which includes data reduction, data presentation, drawing conclusions and verification. Based on the results of the research, a number of conclusions were obtained, including the form of the relevance of original science to period IV chemical elements, so that it could be used as a learning resource. The scientific concepts contained in the original knowledge of blacksmiths include metal elements, electron configurations, metal properties, corrosion, redox reactions, and metal alloys.